AUTOMATISASI KALIBRASI SENSOR SUHU PTC DAN NTC MEMPERGUNAKAN SUMBER TEGANGAN TERPROGRAM DAC7611 - Herman Syahputra; Lazuardi Umar; Rahmondia Nanda Setiadi (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A system calibration of PTC and NTC temperature sensor using a preprogrammable voltage source based on DAC7611 was designed. Temperature sensors of PTC typethermistor used was a type of RS and NTC type was B57962 S282 using a standard voltage divider with resistance to both sensors. Sensor voltage was increased with a step interval of 1V and time equilibrium sensors of 120 s. The characteristic of the sensor were modeled in the form of the curve I(U) based on the self-heating effect (Self-Heating). Results of measurements and modeling using automatic and manual calibration showed two curves coincided, but there was a difference of 5,8mA maximum current for the PTC sensor and 0,552mA for NTC sensor. These resultsindicated that the manufacturing of automatic calibration system worked and only had a small difference to the manual calibration. This was due to the difference in temperature of the ambient.